Perception of Farmers About Quality Seed - R. R. Prajapati , S. M. Patel , Arnab Biswas and M. R. Prajapati, (Indian Journal of Extension Education, 2017)
The study was conducted purposively in Banaskantha district of Gujarat state. Four major crops of the district viz., Potato, Bajra, Castor and Groundnut were selected to study the perception of farmers on quality seeds. These four crops are predominantly grown in Deesa and Vadgam talukas of the district therefore; these two talukas were selected purposively for the study. From each selected taluka eleven villages and from each selected village fifteen farmers were selected randomly. Thus, the final sample of the study consists of 330 farmers. Result revealed that majority of the farmers were middle aged (45.20%) and had primary to secondary level of education (71.50%), had social participation in one organization (62.75%), had small and medium size of land holding (69.70%). The availability, accessibility and affordability of quality seed in case of Pearl millet (bajra) and castor was found good but in case of potato and groundnut it was poorly perceived by the farmers. Further, about three-fourth respondents had medium level of overall perception towards quality seed and adopted quality seed produced either by the seed companies or seed aid organizations.